The Convergence of 5.0 and Forensic Accounting: Leveraging Blockchains for Effective Corruption Prevention in Indonesia - Andaru, F Mario; Utami, Bernadetta Paradintya (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
This research aims to investigate the great potential of blockchain technology as a prevention tool effective corruption in Indonesia by combining blockchain technology and forensic accounting practices. This research will involve in-depth literature analysis to explore understanding of the basic concepts of blockchain and how this technology can be used in forensic accounting practice for prevention corruption. The results of this study are expected can provide deep insight into how blockchain technology can be used as a preventative tool effective corruption in Indonesia. We plan to produce a model that can provide guidance practical for government agencies, organizations, and accounting practitioners in adopting and implementing blockchain in an effort prevention corruption. This research will provide a foundation theoretical and practical use of blockchain as a preventative tool potential corruption in Indonesia.